THE RELATIONSHIP BETWEEN GREEN SPACE DENSITY AND THE PREVALENCE OF RESPIRATORY DISEASES IN LARGE CITIES - Salomova Feruza Ibodullayevna; Sadullayeva Xosiyat Abduraxmanovna (American Journals Publishing, 2025)
The density of green spaces in large cities directly affects the respiratory health of the population. This analytical study statistically assessed the relationship between green space density, PM2.5 concentrations, and the prevalence of respiratory diseases (asthma, chronic obstructive pulmonary disease (COPD), allergic rhinitis) across 25 megacities from 2010 to 2024. Correlation and regression models were applied using WHO (2023), GBD (2024), and advanced epidemiological datasets. The results show that a 10% increase in green space coverage corresponded to a 6–9% reduction in PM2.5 levels and a 4.3–7.1% decrease in respiratory disease prevalence. These findings confirm the strategic importance of urban greening in public health and urban planning policies.
Keywords: Green spaces, respiratory diseases, PM2.5, urbanization, asthma, COPD, epidemiology, urban ecology, correlation, regression.